Three-Dimensional Black-Blood T1-Weighted Turbo Spin-Echo Techniques for the Diagnosis of Deep Vein Thrombosis in Comparison With Contrast-Enhanced Magnetic Resonance Imaging: A Pilot Study. Issue 6 (June 2015) - Treitl, Karla Maria; Treitl, Marcus; Kooijman-Kurfuerst, Hendrik; Kammer, Nora N.; Coppenrath, Eva; Suderland, Elena; Czihal, Michael; Hoffmann, Ulrich; Reiser, Maximilian F.; Saam, Tobias
Abstract : Objectives: The objective of this study was to evaluate the feasibility of a novel 3-dimensional turbo spin-echo technique with isotropic resolution for the diagnosis of deep vein thrombosis (DVT) in comparison with contrast-enhanced magnetic resonance imaging (CE-MRI) and sonography. Materials and Methods: Thirteen patients (8 males, 17–93 years) with proven DVT in duplex ultrasound (n = 11) or with pulmonary embolism and suspected to have DVT (n = 2) were consecutively imaged at 3.0 T with 1.2-mm isotropic-resolution volumetric isotropic turbo spin-echo acquisition (VISTA). Sensitivity (SE), specificity (SP), positive and negative predictive values (PPV and NPV, respectively), Cohen κ, as well as accuracy of VISTA-MRI were calculated and compared with CE-MRI and sonography as a standard of reference. Image quality and diagnostic confidence were assessed on a 4-point scale. Results: Image quality and diagnostic confidence level of VISTA-MRI and CE-MRI were comparable (3.54 vs 3.55 and 3.80 vs 3.77; both P values are nonsignificant). Using CE-MRI as the criterion standard, there was a high agreement between the CE-MRI and the 3-dimensional VISTA examinations for the detection of DVT, with κ of 0.89 for reader 1 and κ of 0.88 for reader 2 (both P < 0.001). The SE, SP, PPV, NPV, as well as accuracy of VISTA-MRI were 92.5%, 97.9%, 89.3%, 98.6%, and 97.1% for reader 1 as well as 90.7%, 97.9%, 89.1%, 98.3%, and 96.8% for reader 2. For both readers, combined comparison of VISTA-MRI and sonography resulted in an SE, SP, PPV, and NPV of 77.8%, 94.8%, 85.4%, and 91.6%, respectively. Conclusions: Volumetric isotropic turbo spin-echo acquisition magnetic resonance imaging can be used to diagnose DVT with good to excellent agreement compared with CE-MRI and sonography. It might be useful when contrast media is prohibited and in patients with suspected thrombosis of the iliac veins, which can be hard to detect with sonography.